(untitled) (Albayan Scientific Journal, 2023)
Many wild plants release some toxins that hinder the growth of other plants, and this phenomenon is called allelopathic. The study aimed to find out whether there are allelopathic effects of thyme plant on the germination and growth of barley plant or not. The results obtained showed that the aqueous extract of a plant has no effect on Stem length and root length of barley crop, while sunflower extract had an effect on barley germination, and the study came to a recommendation that it is possible to use sunflower as a biological control due to the high allelopathicity of sunflower.